Perceived quality framework in product generation engineering: an automotive industry example. (2019) - Stylidis, Kostas; Bursac, Nikola; Heitger, Nicolas; Wickman, Casper; Albers, Albert; Söderberg, Rikard
Abstract : Perceived quality refers to customers' cognitive and emotional responses to a particular design, often also associated with craftsmanship and customer satisfaction. Previous research defined a taxonomy of perceived quality and provided understanding about how engineering design decisions impact customer satisfaction. Furthermore, development of new products is frequently based on carrying over attributes of existing products, either from the same producer or from competitors. Previous research offered a new product development methodology combining variations of subsystems to carry over from existing products. This brief presents how these two lines of research combined to design the central console of the Porsche Panamera automobile and discusses the opportunities and challenges posed in the practical implementation of this research.